Initial development of combinations of sweet orange grafts on citrandarin and tangerineira graft holders (Research, Society and Development, 2021)
In citriculture, diversification of the combination of crowns and rootstocks is a necessity to obtain success in graft taking, to decrease the time of establishment of the plant in the field and to improve the productive potential. Thus, this work aims to evaluate the initial development of combinations of sweet orange tree tops ('Pera D6', Pera rio and Natal) with citrandarin (San Diego) and mandarin (Sunki tropical) rootstocks. The experiment was carried out in a greenhouse belonging to Fazenda Lima, located in the municipality of Capitão Poço, State of Pará. A completely randomized design was used, arranged in a 2x3 factorial scheme, being a citrandarin rootstock (San Diego) and one of mandarin (Sunki tropical) and three cups of sweet orange cultivars ('Pera D6', Pera rio and Natal). The technique used was inverted T-bubbling. After 12 days of the grafting, the graft tape was removed and with 26 days after the grafting, the variables height of the graft, stem diameter of the grafts and quantity of graft leaves were collected. The data obtained were subjected to the Shapiro-Wilk normality test and analysis of variance, the means were compared using the Scott-Knott 5% test, with the assistance of the ASSISTAT software. The combination of 'Pera D6' orange and tropical Sunki mandarin showed the best initial development.